Sequential extraction of compounds of interest from yeast biomass assisted by pulsed electric fields - Berzosa, Alejandro; Delso, Carlota; Sanz, Jorge; Sánchez-Gimeno, Cristina; Raso, Javier (Frontiers in Bioengineering and Biotechnology, 2023)
One strategy to reduce cost and improve feasibility of waste-yeast biomass valorization is to obtain a spectrum of marketable products rather than just a single one. This study explores the potential of Pulsed Electric Fields (PEF) for the development of a cascade process designed to obtain several valuable products from Saccharomyces cerevisiae yeast biomass. Yeast biomass was treated by PEF, which affected the viability of 50 %, 90 %, and over 99 % of S. cerevisiae cells, depending on treatment intensity. Electroporation caused by PEF allowed access to the cytoplasm of the yeast cell without causing total breakdown of the cell structure. This outcome was an essential prerequisite to be able to perform a sequential extraction of several value-added biomolecules from yeast cells located in the cytosol and in the cell wall. After incubating yeast biomass previously subjected to a PEF treatment that affected the viability of 90 % of cells for 24 hours, an extract with 114.91 ± 2.86, 7.08 ± 0.64 and 187.82 ± 3.75 mg/g dry weight of amino acids, glutathione, and protein, respectively, was obtained. In a second step, the extract rich in cytosol components was removed after 24 h of incubation and the remaining cell biomass was re-suspended with the aim of inducing cell wall autolysis processes triggered by the PEF treatment. After 11 days of incubation, a soluble extract containing mannoproteins and pellets rich in β-glucans were obtained. In conclusion, this study proved that electroporation triggered by PEF permitted the development of a cascade procedure designed to obtain a spectrum of valuable biomolecules from S. cerevisiae yeast biomass while reducing the generation of waste.